Willingness to pay and willingness to accept in a patient-centered blood pressure control study - Julie Gleason-Comstock; Alicia Streater; Allen Goodman; James Janisse; Aaron Brody; LynnMarie Mango; Rachelle Dawood; Phillip Levy (BMC, 2017)
Abstract Background Elevated blood pressure is a major risk factor for cardiovascular disease and stroke but patients often discount recommended behavioral changes and prescribed medications. While effective interventions to promote adherence have been developed, cost-effectiveness from the patient's perspective, has not been well studied. The valuation of patient time and out of pocket expenses should be included while performing cost effectiveness evaluation. The Achieve BP study uses the contingent valuation method to assess willingness to accept (WTA) and willingness to pay (WTP) among patients with a history of uncontrolled blood pressure discharged from an urban emergency department and enrolled in a larger randomized controlled trial. Methods WTA and WTP were assessed by asking patients a series of questions about time and travel costs and time value related to their study participation. A survey was conducted during the final study visit with patients to investigate the effectiveness of a kiosk-based educational intervention on blood pressure control. All study patients, regardless of study arm, received the same clinical protocol of commonly prescribed antihypertensive medication and met with research clinicians four times as part of the study procedures. Results Thirty-eight patients were offered the opportunity to participate in the cost-effectiveness study and all completed the survey. Statistical comparisons revealed these 38 patients were similar in representation to the entire RCT study population. All 38 (100.0%) were African-American, with an average age of 49.1 years; 55.3% were male, 21.1% were married, 78.9% had a high school or higher education, and 44.7% were working. 55.9% did not have a primary care provider and 50.0% did not have health insurance. Time price linear regression analysis was performed to estimate predictors of WTA and WTP. Conclusions WTP and WTA may generate different results, and the elasticities were proportional to the estimated coefficients, with WTP about twice as responsive as WTA. An additional feature for health services research was successful piloting in a clinical setting of a brief patient-centered cost effectiveness survey. Trial registration https://clinicaltrials.gov . Registration Number NCT02069015 . Registered February 19, 2014 (Retrospectively registered).